Duration and Magnitude of Opioid Use After Minimally Invasive Sacroiliac Joint Fusion - Benson, Dillon; Litvak, Audrey; Zhang, Douglas; Johnson, Christopher; El Dafrawy, Mostafa; Lee, Michael (Spine (Philadelphia, Pa. 1976), 2024)
Retrospective cohort study performed in a nationwide insurance claims database. To evaluate the duration and magnitude of post-operative opioid prescriptions after minimally invasive surgical sacroiliac joint fusion (MIS SIJF) as compared to other common spine surgeries. MIS SIJF has been reported to significantly improve quality of life and reduce pain. However, there is a paucity of reported data on post-operative opioid use in patients undergoing MIS SIJF for sacroiliac joint dysfunction. A nationwide insurance claims database was queried to identify 4,666 patients who underwent MIS SIJF. Patients were stratified by pre-operative opioid use: Opioid naïve, sporadic use, or chronic use were respectively defined as 0,1, or≥2 opioid prescriptions filled within 6 months prior to surgery. Duration of opioid use was defined by the time between MIS SIJF and last opioid prescription filled while magnitude of opioid use was determined by milligram morphine equivalents filled by 30 days post-operation. This opioid use data was compared to that of other common spine surgeries. Patients undergoing MIS SIJF continued to fill opioid prescriptions 1-year post-operatively at significantly higher proportions than those undergoing other common spine procedures assessed by prior literature within each of the pre-operative opioid use cohorts (chronic: 73% vs. 49-62%; P <0.0001, sporadic: 39% vs. 23-28%; P <0.0001, opioid naïve: 22% vs. 15-18%; P <0.0001). Chronic users filled the highest opiate dosages during the 30-day post-operative period, filling on average 64.75 MME/d compared to 19.75 MME/d and 24.25 MME/d by the opioid naïve and sporadic users, respectively. After MIS SIJF, opioid naïve patients use fewer opioids and for a shorter period of time compared to patients with sporadic or chronic pre-operative opioid use. MIS SIJF may result in less effective pain reduction when compared to other common spine surgeries evaluated via identical methodology. 3.